THE EFFECT OF FLOW SPEED AGAINST TO THE PERFORMANCE OF STOW NETS - ', Pujiono; ', Nofrizal; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTvuji.pujiono@yahoo.comThis research was conducted on Agustus 2014, which is held in the Laboratory Fishing Gear Materials, The Faculty of Fisheries and Marine Sciences, University of Riau. The purpose of this study was to determine the performance of stow nets fishing gear in the water, therefore it can infer the ideal flow velocity for this fishing gear. This study used an experimental method to determine the performance of stow nets fishing gear which is tested in the flume tank by using an impeller rotation speed was 5-50 Hz and the flow velocity was 2.7-246.1 cm/sec. The results were obtained that flow velocity made the effect on the position, the movement and the shift of stow nets fishing gear too. The ideal flow velocity for stow nets fishing gear was 44.3 cm /sec, while the flow velocity was 2.7 cm /sec it made the mouth of filter nets fishing gear started to open in the flume tank on the right time.Keyword : Flow velocity, performance, stow nets, flume tank.